Форма проявления толерантности - Абидова, З.А. (SCIENCE and SOCIETY, 2024)
In this article, an attempt is made to systematize the forms of manifestation of tolerance. According to the form of manifestation of tolerance as a process, the author conditionally divides them into three types: a response that has a more emotional component, an attitude that has a more cognitive component and an action that has a more behavioral component.
Keywords: tolerance; response; attitude; actions; emotional; cognitive; behavioral component